BMP-2 incorporated biomimetic CaP coating functionalized 3D printed Ti6Al4V scaffold induces ectopic bone formation in a dog model. (March 2022) - Gu, Yifei; Wei, Lingfei; Zhang, Zheru; Van Dessel, Jeroen; Driesen, Ronald B.; Lambrichts, Ivo; Jacobs, Reinhilde; Tian, Lei; Sun, Yi; Liu, Yuelian; Politis, Constantinus
Graphical abstract: Highlights: A Ti6Al4V scaffold with optimal designing parameters and mechanical properties similar to cancellous bone was 3D-printed. To improve biocompatibility, a porous micro/nanostructured biomimetic calcium phosphate coating was applied to the scaffold. Using the coating as a carrier, bone morphogenic protein-2 was consistently and uniformly released in a cell-mediated manner. The bone morphogenic protein-2 integrated coating induced an even distribution of new bone formation within the scaffold. Abstract: The use of Ti6Al4V in bone engineering is limited, due to the biological inertia of the surface. In this study, a porous Ti6Al4V scaffold with mechanical properties similar to cancellous bone was designed and 3D-printed. Under physiological conditions, the scaffold was immersed firstly in a 5-fold-concentrated simulated body fluid, then in a supersaturated CaP solution containing BMP-2, to form a bone-like porous micro/nano structured biomimetic coating on the surface. Scaffolds were implanted in the muscle pouches created in six beagle dogs and were retrieved four weeks later for histologic and histomorphometric analysis. Results showed that BMP-2 integrated biomimetic CaP coating induced ectopic bone formation, which was absent in other two groups. Soft tissue infiltrated the scaffold's outside 1 mm layer, while the new-formed bone was evenly distributed in the longitudinal and horizontal directions within the rest of the scaffold based on BA/TA, BIC and BA measurements. In conclusion, the BMP-2 incorporated biomimetic CaP coating creates a micro/nano surface structure on the Ti6Al4V scaffold, which helps to increase biocompatibility. The integrated BMP-2 is capable of inducing ectopic bone formation in vivo. The proposed combination may have the potential for bone reconstruction, but further studies are needed to explore its clinical applicability.